Wśród czerni i złota - w kręgu poetyki Stanisława Staszewskiego = Among black and gold - on Stanisław Staszewski`s poetics - Kubiak, Maciej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article aims to present the artistic works of Stanisław Staszewski and his poetics defined within the semantic field of loneliness, eroticism and longing. This study analyses the output of Staszewski that comes from original (also unpublished) recordings and examines texts from the volume of poetry "Samotni ludzie, wiersze i piosenki" ["Lonely people, poems and songs"] (2015). This text aims to look at the formal music-textual aspect of works by Stanisław Staszewski. The sketch tries to contribute to general knowledge of the artistic activity of Stanisław Staszewski and its results.
Keywords: Staszewski, Stanisław (1925-1973); teksty piosenek; wiersze; poetyka; oddziaływanie; lyrics; poems; poetics; impact